Congenital absence of the skin: a case series report - Jesús Vicente Redondo Sedano; María Dolores Delgado Muñoz; Alicia Gómez Sánchez; Sara Monserrat Proaño Landazuri; María López Maestro; Jesús Rodríguez Calvo; Cecilia Castellano Yáñez; Andrés Gómez Fraile; María Eunate Marti Carrera (SpringerOpen, 2022)
Abstract Background Extracranial congenital skin defects, defined as aplasia cutis congenita (ACC), are a rare clinical entity. The form of presentation varies among patients according to the causal agent and the point during pregnancy at which the defect occurs. We present a series of cases of noncranial ACC, analysing its possible etiopathogenesis and the evolution of the lesions. Materials and methods This is a retrospective review of cases of extracranial ACC at a tertiary hospital. Case presentation Patient 1 is a full-term newborn of a monochorionic diamniotic gestation with the death of one foetus at 14 weeks of gestational age. Physical examination revealed two skin defects located on the posterior aspect of both thoraco-abdominal flanks. Patient 2 is a full-term newborn presenting with an ulcer on the nasal tip and cephalic extension on a follow-up pregnancy ultrasound. Patient 3 is a full-term newborn of a monochorionic diamniotic gestation with twin feticide due to encephalocele, presenting an ulcer on the lateral aspect of the proximal third of her right leg. The gestation associates severe oligohydramnios due to premature rupture of the membranes and breech presentation. Patient 4 is a full-term newborn with an ulcer on the left antecubital fossa with no relevant gestational history. Conclusion The analysis of the obstetric history and the clinical presentation of the lesions helps to guide the aetiopathogenic diagnosis of congenital skin defects. The increased intracompartment pressure in the limbs is related to the increased severity of skin lesions and musculoskeletal and nerve involvement. Conservative treatment is related to a good prognosis for the lesions.